Paracetamol – toxicity and microbial utilization. Pseudomonas moorei KB4 as a case study for exploring degradation pathway. (September 2018) - Żur, Joanna; Wojcieszyńska, Danuta; Hupert-Kocurek, Katarzyna; Marchlewicz, Ariel; Guzik, Urszula
Abstract: Paracetamol, a widely used analgesic and antipyretic drug, is currently one of the most emerging pollutants worldwide. Besides its wide prevalence in the literature only several bacterial strains able to degrade this compound have been described. In this study, we isolated six new bacterial strains able to remove paracetamol. The isolated strains were identified as the members of Pseudomonas, Bacillus, Acinetobacter and Sphingomonas genera and characterized phenotypically and biochemically using standard methods. From the isolated strains, Pseudomonas moorei KB4 was able to utilize 50 mg L −1 of paracetamol. As the main degradation products, p -aminophenol and hydroquinone were identified. Based on the measurements of specific activity of acyl amidohydrolase, deaminase and hydroquinone 1, 2-dioxygenase and the results of liquid chromatography analyses, we proposed a mechanism of paracetamol degradation by KB4 strain under co-metabolic conditions with glucose. Additionally, toxicity bioassays and the influence of various environmental factors, including pH, temperature, heavy metals at no-observed-effective-concentrations, and the presence of aromatic compounds on the efficiency and mechanism of paracetamol degradation by KB4 strain were determined. This comprehensive study about paracetamol biodegradation will be helpful in designing a treatment systems of wastewaters contaminated with paracetamol. Highlights: Pseudomonas moorei KB4 degrades 50 mg L −1 of paracetamol. Acylamidohydrolase, deaminase & hydroquinone 1, 2-dioxygenase transform paracetamol. p -aminophenol and hydroquinone are the main degradation products of paracetamol. Drug is degraded in the presence of phenol, 4-hydroxybenzoate, 4- and 2-chlorophenol.